Last Mile Delivery with Autonomous Vehicles: Fiction or Reality? - Gramatikov, Sasho; Kitanovski, Ivan; Mishkovski, Igor; Jovanovik, Milos (Ss. Cyril and Methodius University in Skopje, Faculty of Computer Science and Engineering, Republic of North Macedonia, 2019)
Autonomous vehicles (AVs) are a disruptive technology of the 21-st century that are beginning the next revolution of the transportation of people and goods. Their presence has a particular impact on the future directions of development of E-commerce. The number of online orders is in a steep incline, and so is the necessity to deliver goods to the customer in an efficient and environmental friendly way. Using autonomous drones, pods and vans for delivery of goods has already become reality. But, what is the state of the art of the companies offering these services and how do people feel about it? The aim of this paper is to make an overview of the business models of the companies developing AVs for Last Mile Delivery (LMD) of goods and to find out what is the attitudes of the online customers towards using AVs for delivery of their goods.
Keywords: Autonomous vehicles; Last mile delivery; Business model; Survey; Public opinion